Investigation of The Limiting Behavior of The Sequence of Density Ratios in A Family of Non-Central t-Distribution - Sunardi Wirjosudirdjo (Journal of Mathematical and Fundamental Sciences, 1964)
Abstract. Let X1, X2, "¦..be a sequence of noncentral t-distributed random variables with parameter Î¸. In this paper we investigate the limiting behavior of density ratios of X0. This is an example of the family of distributions discussed in [4].Here, we derive the results of David and Kurskall [2] in a slightly more general form and a stronger result is obtained, namely: If Î¸1 < Î¸2 are two parameters and Rn(Î¸1,Î¸2) is the density ratio of Xn, then there is  Î¸0 such that the limit of Rn is 0 with respect  to Î¸<Î¸0 and is âˆž  with respect  to Î¸>Î¸0. With respect to Î¸=Î¸0, the limit infimum is 0 and the limit supermum is âˆž. It is also shown that Î¸0 is between 0 and ½ (Î¸1+Î¸2). Ichtisar. Misalnja X1, X2 "¦ adalah barisan variabel random jang mempunjai distribusi t jang nonsentral dengan parameter Î¸. Maksud dari karangan ini adalah menjelidiki sifat2 limit rasio fungsi kepadatan dari Xn tersebut. Hal ini merupakan tjontoh dari matjamnja family distribusi jang dibitjarakan dalam karangan [4]. Djuga karangan ini merupakan pembitjaraan lebih landjut dari [2], dimana David & Kruskal membuktikan bahwa sequential probability ratio test dari distribusi t akan berhenti dengan kemungkinan satu. Sifat limit dari tjontoh famili distribusi disini lebih kuat dari di [4], dan dapat diterangkan sbb. : Misalkan Î¸1 < Î¸2 adalah dua parameter dan Rn (Î¸1, Î¸2) adalah rasionkepadatan Xn dari Î¸2 dan Î¸1. Maka terdapat Î¸0 sehingga limit dari Rn sama dengan 0 terhadap Î¸ < Î¸0 dan sama dengan âˆž terhadap Î¸ > Î¸0. Sedang terhadap Î¸0 limit infimumnja sama dengan 0 dan limit supremumnja adalah âˆž. Letak Î¸ ini diantara 0 dan 1/2 (Î¸1 + Î¸2), sehingga hal jang terachir ini akan menghilangkan sangkaan orang mengenai letak simetrinja Î¸0 diantara 01 dan 02.